2012
DOI: 10.1016/j.jiph.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of water-pipe smoking among high school students in Saudi Arabia

Abstract: Objective: To identify the prevalence and predictors of the water-pipe (WP) smoking epidemic in the Kingdom of Saudi Arabia (KSA). Methods: A cross-sectional study conducted with 16-18 year-old high school students in Riyadh, Saudi Arabia. Results: Of the 1272 participants, 414 (33.0%) reported having tried WP smoking. Of this group, 141 (34.1%) were female and 273 (65.9%) were male. Further, 129 (10.2%) students were current WP smokers who had used at least one rock in the past month; 20 were female (1.6%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 23 publications
7
28
3
Order By: Relevance
“…It has very few members of other ethnic groups, and has rigid ideas about tobacco smoking especially among adolescents and females. In a study in Saudi Arabia [18], half of the students smoked WPs at cafés which shows how cafés in the Middle East are the main place for WP smoking. On the other hand, half of the females, who are socially restricted in Saudi Arabia, smoked WPs in their homes in contrast in our study where just 14.2% of the current female WP smokers have smoked at their homes and 40.8% smoked WP at coffee shops which broke the rules and served WP to their under-age customers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has very few members of other ethnic groups, and has rigid ideas about tobacco smoking especially among adolescents and females. In a study in Saudi Arabia [18], half of the students smoked WPs at cafés which shows how cafés in the Middle East are the main place for WP smoking. On the other hand, half of the females, who are socially restricted in Saudi Arabia, smoked WPs in their homes in contrast in our study where just 14.2% of the current female WP smokers have smoked at their homes and 40.8% smoked WP at coffee shops which broke the rules and served WP to their under-age customers.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of WP smoking in developing countries increases by 3.5% annually, mainly among youth [2,[15][16][17]. For instance, in Saudi Arabia, the prevalence of WP smoking between 2002 and 2007 increased from 6.8% to 8.7% among 13-15 year-old school students [17,18]. The national fact sheets from the Global School Based Student Health Survey (GYTS) among middle school (grades 1 and 2) and high school (grade 1) students in Iran in 2007 showed that 16.5% of students were current (smoked WP within last 30 days) WP smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis showed marital status did not significantly influence the practice of water pipe smoking among Malaysian University Students (8). In addition, we noticed some statistically significant raising trend of water-pipe Smoking a risk of 1 st year students to 5 th year students which the prevalence in 1 st year is 3.4% and it became 16% in 5 th year.…”
Section: Discussionmentioning
confidence: 65%
“…Water-pipe is cheap and widely available, facilitating its use among youth and individuals. In 2010, a study shows the prevalence of water pipe smoking was 37.5% among non-medical students(6) and a study shows that cigarette and water pipe smoking prevalence rate of 61.9% for males and 10.7% for females (8), Another study shows that 414 university students were reported as water pipe smokers (9) the study showed among Medical students it was reported that the prevalence of water pipe was 28.6%(5) which shows that is our estimate indicate the prevalence of smoking water pipe less in KSU medical students 12.1% . In 2011, a study was done among male medical students which showed results of 12.6% were reported as Shisha smokers and 4% were smoking both shisha and cigarette.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation